Bionomic responses of Spodoptera frugiperda (J. E. Smith) to lethal and sublethal concentrations of selected insecticides - Fiaboe, K.R.; Fening, K.O.; Gbewonyo, W.S.K. (PLOS ONE, 2023)
Since 2016, the invasive insect Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctui dae) from the Americas has made maize production unattainable without pesticides in parts of Sub-Saharan Africa and Asia. To counteract this pest, farmers often resort to the use haz ardous pesticides. This study aimed to investigate botanicals, microbials, and semi-syn thetic insecticides in Ghana for pest control without harming local ecosystems. Under laboratory and on-station conditions, the present study evaluated the acute and sublethal responses of S. frugiperda to: (i) Pieris rapae Granulovirus (PrGV) + Bacillus thuringiensis sub sp. kurstaki (Btk) 5 WP, (ii) Btk + monosultap 55 WP, (iii) ethyl palmitate 5 SC, (iv) aza dirachtin 0.3 SC, (v) acetamiprid (20 g/l) + λ-cyhalothrin (15 g/l) 35 EC, (vi) acetamiprid (30 g/l) + indoxacarb (16 g/l) 46 EC, and (vii) emamectin benzoate 1.9 EC. The results showed that at 96 hours post-exposure emamectin benzoate-based formulation has the highest acute larvicidal effect with lower LC50 values of 0.019 mL/L. However, the results suggested strong sublethal effects of PrGV + Btk, azadirachtin, and ethyl palmitate on the bionomics of S. frugiperda. Two seasons on-station experiments, showed that the semi-synthetic ema mectin benzoate and the bioinsecticide PrGV + Btk are good candidates for managing S. frugiperda. The promising efficacy of emamectin benzoate and PrGV + Btk on the bionomics of S. frugiperda in the laboratory and on-station demonstrated that they are viable options for managing this pest.
Research Article
Keywords: Spodoptera frugiperda; botanicals; botanicals; Ghana; Americas